Evaluation of the Impact of Online Monitoring on Lead Time in an Experimental Assembly Line - Esa Belia; Akbar Maulana Yusuf; Mohammad Fauzan Aulialdi; Muhammad Arifudin Lukmana (Universitas Medan Area, 2026)
Advances in modern manufacturing require real-time visibility into production data to avoid delayed decision-making and inventory buildup; however, current monitoring technologies are expensive and complex for small industries. This study was conducted on an experimental assembly line by designing, implementing, and evaluating an IoT-based online monitoring system. The experiment compared the 4-station toy airplane assembly process before and after system implementation, with time data validated using the adequacy test, Shapiro-Wilk normality test, and paired t-test. The analysis results showed a significant improvement in production flow performance, with a reduction in lead time at each workstation of 25,21%, 22,37%, 21,91%, dan 30,35%., respectively. With real-time data transmission to a cloud database, early detection of bottlenecks through work-in-process monitoring can be performed, which subsequently improves the balance of the assembly line.